Comparison of fecal microbiota of SPF and non-SPF Beagle dogs - Yu, Cuilian; Guo, Zhongkun; Lei, Zhan; Mao, Xiaolong; Chen, Shumin; Wang, Kezhou (Frontiers in Veterinary Science, 2023)
Microbial colonization of animal intestine impacts host metabolism and immunity. The study was aimed to investigate the diversity of the intestinal microflora in specific pathogen free (SPF) and non-SPF Beagle dogs of different ages by direct sequencing analysis of the 16S rRNA gene. Stool samples were collected from four non-SPF and four SPF healthy Beagle dogs. From a total of 792 analyzed Operation taxonomic units, four predominant bacterial phyla were identified: Firmicutes (75.23%), Actinobacteria (10.98%), Bacteroidetes (9.33%), and Proteobacteria (4.13%). At the genus level, Streptococcus, Lactobacillus, and Bifidobacterium were dominated. Among which, Alloprevotella, Prevotella_9, and Faecalibacterium were presented exclusively in non-SPF beagles, with potentially anti-inflammatory capability, which could protect non-SPF beagles from complex microbial environment. The number and diversity of intestinal flora for non-SPF Beagle dogs were the highest at birth and gradually decreased with growth, whereas the results for the SPF beagle samples were the opposite, with the number and diversity of intestinal microbiota gradually increases as beagles grow. In a nutshell, the microbial complexity of the rearing environment can enrich the gut microbiota of beagles, many of which are anti-inflammatory microbiota with the potential to increase the adaptability of the animal to the environment. However, the gut microbiota of SPF beagles was more sensitive to environmental changes than that of non-SPF beagles. This study is of great significance for understanding the bionomics of intestinal microflora in non-SPF and SPF beagles, improving the experimental accuracy in scientific research.